Demystifying MIMO - Allen, B; Malik, W; Smith, P; Edwards, D (2006)
The importance of multiple-input multiple-output (MIMO) to exploit the spatial diversity of digital communication system, is discussed. The continued demand for capacity that is driven by the convergence of mobile phones, the Internet and multimedia services have led to the invent of MIMO. MIMO assures to improve the bit-error rate and/or data throughput and reduce the overall cost of transmission. As it functions efficiently in a wireless system with four transmit and four receive antennas operating in ideal propagation conditions, that is with lots of multipath, and with a signal-to-noise ratio of 12 dB at 10% channel outage, which has a spectral efficiency of 1b/s/Hz. The spectral efficiency of MIMO grows linearly with the number of antennas, compared to logarithmic growth for systems with multiple antennas. The inclusion of space time codes into communication system has enhanced the performance of transmitter, that also helps to improve the overall performance of systems.